TECHNICAL VOCATIONAL EDUCATION AND TRAINING INSTITUTIONS’ CONTRIBUTION TO PROMOTING SUSTAINABLE DEVELOPMENT - Kintu, Denis (Machakos University, 2019)
The concept of sustainable development can be possible if people possess the necessary skills and competences for work in a sustainable manner. Technical, Vocational Education and Training (TVET) has been identified as the type of education that can contribute to the development of a workforce that is skilled and can embrace the ideas of sustainability. In this paper, the researcher presents ideas developed through a plenary discussion with 12 master’s students at his university about the role TVET institutions can play through their traditional roles of teaching and research. The paper reviews literature and explores the concept and concerns for sustainable development, the models for sustainability and sustainable development, and identifies the role TVET institutions can play in the transformation to sustainable societies. Further, the paper identifies the challenges TVET institutions face in imparting sustainability skills and concludes by suggesting possible solutions to the challenges
Keywords: Technical; Vocational Education and Training; Sustainable Development